Prof. Zeynep Tuncer's visit: collaboraton beyond boudaries - Abdul Rahim, Elin Eliana; Mahmud, Murni; Azuddin, Muna (KICT, IIUM, 2025)
Prof. Zeynep Tuncer from Baden-Wuerttemberg Cooperative State University (DHBW), Germany, visited the Kulliyyah of Information and Communication Technology (KICT), IIUM, from 11 to 13 August 2025. The visit was hosted by the Perceptive and Sentiment Computing (PSC) Research Group together with the Pervasive Computing for Brain Development Research Group (PCBDG).